Bladder wall thickness in women with symptoms of overactive bladder and detrusor overactivity: Results from the randomised, placebo‐controlled shrink study. Issue 7 (21st July 2015) - Robinson, Dudley; Oelke, Matthias; Khullar, Vik; Wijkstra, Hessel; Tretter, Reiner; Stow, Bridget; Compion, Gerhard; Tubaro, Andrea
Abstract : Aims: Measurement of bladder wall thickness (BWT) by transvaginal ultrasound (TVUS) may be a less invasive method to diagnose overactive bladder (OAB) or detrusor overactivity (DO) and monitor response to therapy. This study assessed whether treatment with solifenacin affects BWT. Methods: This was a double‐blind, randomised, placebo‐controlled, phase 4 study. Adult women with OAB symptoms received solifenacin 5 or 10 mg or placebo once daily for 12 weeks. The co‐primary endpoints were change from baseline to Week 12 in TVUS‐measured BWT and urinary nerve growth factor. Only results for BWT are presented here. Results: Overall, 547 patients were randomised, 501 patients had a baseline BWT measurement, and change from baseline could be calculated for 478 patients. Mean BWT at baseline was 5.08 mm (range 2.2–11.1, SD = 1.14) and was normally distributed. A significant reduction in BWT from baseline to 12 weeks versus placebo was observed with solifenacin 5 mg (–0.42 vs. –0.16 mm, P  = 0.03), but not with the 10 mg dose or with pooled solifenacin, considered the primary comparison. Both solifenacin doses were associated with improvements in efficacy and patient satisfaction endpoints versus placebo. Solifenacin was well tolerated, with dry mouth being the most common adverse event. Conclusions: There was no consistent effect of solifenacin on BWT in women with OAB/DO, despite improvements in efficacy endpoints. This study suggests that routine clinical assessment of BWT with TVUS for monitoring the effects of OAB/DO treatment is not clinically useful. Neurourol. Urodynam. 35:819–825, 2016 . © 2015 Wiley Periodicals, Inc.